HUBUNGAN PENDIDIKAN DAN PENGETAHUAN IBU DENGAN PERAWATAN TALI PUSAT PADA BAYI BARU LAHIR - Turiyani; Rani Oktarina (LPPM STIKes Mitra Adiguna, 2024)
According to the World Health Organization (WHO), neonatal mortality contributes 59% to infant mortality where one of the biggest causes is neonatal tetanus, an infection of the umbilical cord that occurs in infants. The aim of the study was to determine the relationship between education and knowledge of mothers and care for the umbilical cord in newborns at BPM Irma Suryani Prabumulih City in 2023. The research method is analytic in nature, using a cross sectional approach. The population of this study were mothers giving birth at BPM Irma Suryani Prabumulih City in 2023. The number of samples in this study were 42 respondents. Sampling using Accidental sampling method. Research instruments in the form of checklists and questionnaires. The results of the study based on univariate analysis found that out of 42 respondents, there were 8 respondents (19%) who did not perform cord care and 34 respondents (81%) who did cord care, there were 35 persons (83.3%) who had higher education and 7 people (16.7%) have low education, there are 33 people (78.6%) who have knowledge and 9 people (21.4%) who have less knowledge. From the bivariate analysis, it was known that of the 35 respondents who had a good education, there were 32 respondents (76.2%) who performed umbilical cord care, while of the 7 respondents who had low education, there were 2 respondents (4.8%) who performed umbilical cord care and from 33 respondents with good knowledge there were 31 respondents (73.8%) who performed umbilical cord care while of the 9 respondents who had less knowledge there were 3 respondents (7.1%) who performed umbilical cord care. In conclusion, there is a significant relationship between mother's education and cord care with a P value 0.001 < ? 0.05, there is a significant relationship between knowledge and cord care with a P value 0.000 < 0.05. Midwives are expected to increase counseling and socialize about umbilical cord care for newborns in the community. Keywords : Umbilical cord care, education, knowledge